THE DEVELOPMENT OF SUSTAINABLE DESIGN DECISION TOOL FOR PUBLIC BUILDINGS IN INDONESIA - Hamdi Akmal Lubis (Teras Jurnal : Jurnal Teknik Sipil, 2013)
Sustainable building has become a catchphrase in many countries. Issue on sustainability has attracted researchers from industry and academia in recent years, and the number is still growing. Despite different definitions of sustainable building, quality improvement of the environment, economy, and social well-being are always seen as three major affecting factors. As part of a larger future research framework, the result of this preliminary research work suggested that a low-cost design decision tool is worth researching. This paper will first, review some of assessment tools currently available today and discuss a new research direction for optimizing the application of those three factors into project appraisal process by utilizing Life- Cycle Costing (LCC) analysis and second, outline research methodology for the development of a decision tool in selecting sustainable options for public buildings design in Indonesia.Keywords: Sustainable building, life-cycle costing, decision support tools, construction investment